Ubiquity or not ubiquity: That is the question - Sleith, Robin S.; Katz, Laura A. (Molecular ecology, 2019)
The nature of population structure in eukaryotic microbes has been the subject of intense debate, but until recently the tools to test these hypotheses were either problematic (e.g., allozymes that cannot detect all genetic changes) or beyond financial and technological limits of most laboratories (e.g., high throughput sequencing). In a recent issue of Molecular Ecology, Craig et al. (2019) use a genomic approach to investigate the population structure of a model alga, the chlorophyte Chlamydomonas reinhardtii (Figure 1). Using high throughput sequencing, read mapping, and variant calling, they detected strong signals of differentiation at a continental scale, while local patterns of admixture were complex. Population genomic techniques such as these have not been used extensively in studies of microbial eukaryotes and the fields of conservation genetics and evolution stand to benefit vastly from the adoption of these techniques to studies of diverse protist lineages.